Fabric topgraphy influence on nanofibers deposition - Ljungerg, Ida; Sánchez-Martínez, Ainhoa; Martínez-González, Inés; Mínguez-García, David; Montava, Ignacio; Díaz-García, Pablo (Wydawnictwo Politechniki Łódzkiej, 2022)
Interest in nanotechnology has increased in recent years and the textile sector has not been left out of this technology. Obtaining nanofibers opens up multiple applications in fields such as filtration. However, due to the fragility of said nanofibers, conventional textiles can serve as a support for the created nanofiber net. In this work we intend to demonstrate the influence of the weave pattern on the homogeneity of nanofibers deposited on the fabric. Two fabrics characterised by wave patterns showing different topography are studied. Authors demonstrate there is a strong influence of topography on the nanofibers deposition. Nanofibers tend to cover wave´s fibres in a higher plane first and it require longer periods to find some fibres on lower planes.
Keywords: roughness; electrospinning; polyvinyl alcohol; coating; chropowatość; elektroprzędzenie; alkohol poliwinylowy; powlekanie